LEGAL PROTECTION FOR WOMEN AND CHILDREN VICTIMS OF HUMAN TRAFFICKING IN THE JURISDICTION OF MEDAN - Tani Erinawaty Saragi; Jaminuddin Marbun; Bachtiar Simatupang (JURNAL PROINTEGRITA, 2019)
The problem of trafficking in women and children or known as trafficking in person lately appears to be a problem that is much debated both at national and international levels and is said to be a form of slavery today and violating human rights. So that the formulation of the problem that can be raised is related to the legal phenomenon, namely: 1). What is the legal protection of women and children victims of trafficking currently in the jurisdiction of the Medan City Police Resort? 2). What are the factors that cause the trafficking of women and children in the jurisdiction of the Medan City Police Resort, and 3). What are the government's policies and the role of the community in overcoming the problem of the rampant level of trafficking in women and children in the jurisdiction of the Medan City Big City Resort? This research is descriptive and is seen from its objectives including empirical legal research. The location of this research was carried out at the Medan Big City Resort Police North Sumatra Province. The types of data used include primary data and secondary data. The method of collecting data is through interviews and library research, both books, legislation, papers, results of previous research, documents, and so on. The results of this study indicate that the discussion on the issue of regulation of legal protection for children and women victims of human trafficking crimes is spread in several laws and regulations that are both general and specific in nature, such as: the Criminal Code, Law No. 21 of 2007 concerning Eradication of Crime in Trafficking in Persons, Act No. 13 of 2006 concerning Protection of Witnesses and Victims. The factors that cause child and female trafficking are divided into two, namely internal factors and external factors internal factors are individual factors, economic factors, family factors, educational factors, lifestyle factors and free association, while external factors are environmental factors, cultural factors, factors weak law enforcement, marriage at a young age, social conflict and war, mass media. Government policy is a protection policy for victims whose essence is an integral part that cannot be separated from protection policies. Based on this concept, the role of the state in creating a social welfare is not only limited to fulfilling the material needs of its citizens, but more than that for the fulfillment of a sense of comfort and security in activities. Indonesia has a law specifically regulating the Protection of Victims of Crimes, namely through Law No. 13 of 2006 concerning Protection of witnesses and victims. The Role of the Community As a deterrent to child trafficking, with more attention to child trafficking crimes, the community environment can overcome and prevent the rampant occurrence of child trafficking; As a protector of children victim so ftrafficking.